UMP seals cooperation with 6 universities in Egypt, Ireland - UMP, PNC
Planning activities in promoting the university internationally. “Internationalization is important in charting the course for a university to be recognized and ranked globally. “Strategic international academic and research co-operations are the bridge for UMP to elevate academic excellence and boost the efforts to promote the university as an international education hub,” the VC further explained.